The Diverse Major Histocompatibility Complex Haplotypes of a Common Commercial Chicken Line and Their Effect on Marek’s Disease Virus Pathogenesis and Tumorigenesis - Bertzbach, Luca D.; Tregaskes, Clive A.; Martin, Rebecca J.; Deumer, Undine-Sophie; Huynh, Lan; Kheimar, Ahmed M.; Conradie, Andelé M.; Trimpert, Jakob; Kaufman, Jim; Kaufer, Benedikt B. (Frontiers in Immunology, 2022)
The major histocompatibility complex (MHC) is crucial for appropriate immune responses against invading pathogens. Chickens possess a single predominantly-expressed class I molecule with strong associations between disease resistance and MHC haplotype. For Marek’s disease virus (MDV) infections of chickens, the MHC haplotype is one of the major determinants of genetic resistance and susceptibility. VALO specific pathogen free (SPF) chickens are widely used in biomedical research and vaccine production. While valuable findings originate from MDV infections of VALO SPF chickens, their MHC haplotypes and associated disease resistance remained elusive. In this study, we used several typing systems to show that VALO SPF chickens possess MHC haplotypes that include B9, B9:02, B15, B19 and B21 at various frequencies. Moreover, we correlate the MHC haplotypes to MDV-induced disease and lymphoma formation and found that B15 homozygotes had the lowest tumor incidence while B21 homozygotes had the lowest number of organs with tumors. Finally, we found transmission at variable levels to all contact birds except B15/B21 heterozygotes. These data have immediate implications for the use of VALO SPF chickens and eggs in the life sciences and add another piece to the puzzle of the chicken MHC complex and its role in infections with this oncogenic herpesvirus.